AFFECTIVE WORK AND ACCESS TO EXCELLENCE — Reorganizing Nordic Welfare - Hjort, Katrin Erna (Advances in Social Sciences Research Journal, 2019)
In the Nordic countries of the 20th century, the caring businesses have usually been handled by women in families or by public institutions of the welfare state. In the 21st century, however, care is becoming a real business. The affective work of education, health and social services is organized by the competitive state or in private welfare enterprises. The economization of welfare leads to the rationalization of work processes and the selection of services and clients. The consequences for the professionals as well as the clients are ambiguous. On one hand, hyper-professionals are developing highly specialized work with the potential to extend human life capacities almost infinitely. On the other hand, sub-professionals are still doing more standardized jobs, and the selection between clients is decreasing. Access to excellent care becomes the central issue, and both professionals and the public are confronted with new ethical challenges.